2014
DOI: 10.1002/mame.201400291
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically and Thermally Enhanced Multiwalled Carbon Nanotube–Graphene Hybrid filled Thermoplastic Polyurethane Nanocomposites

Abstract: Multiwalled carbon nanotube (MWCNT)–chemically reduced graphene oxide (CRGO) hybrid in different weight ratios were prepared by solution mixing. MWCNT–CRGO (1:1) hybrid exhibited better dispersion stability in dry THF and characterized. Subsequently, it was used as reinforcing filler in thermoplastic polyurethane (TPU) nanocomposites by solution intercalation. Further investigations showed that 0.25 and 0.50 wt.‐% MWCNT–CRGO (1:1) loaded TPU exhibit significant improvement in thermal stability (40 °C at 50% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 70 publications
3
49
2
Order By: Relevance
“…[3][4][5][6][7][8][9] The contribution of interphase to mechanical properties of nanocomposites is considerable, due to the high interfacial area at polymernanoparticles interfaces. [10][11][12][13][14][15][16][17][18][19][20] It was reported that the interphase volume fraction exceeds the nanoparticle volume fraction in some samples demonstrating that the mechanical properties are significantly improved by both nanoparticles and interphases. [21] Therefore, many researchers have studied the interphase properties and its contribution to the mechanical properties of polymer nanocomposites.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] The contribution of interphase to mechanical properties of nanocomposites is considerable, due to the high interfacial area at polymernanoparticles interfaces. [10][11][12][13][14][15][16][17][18][19][20] It was reported that the interphase volume fraction exceeds the nanoparticle volume fraction in some samples demonstrating that the mechanical properties are significantly improved by both nanoparticles and interphases. [21] Therefore, many researchers have studied the interphase properties and its contribution to the mechanical properties of polymer nanocomposites.…”
mentioning
confidence: 99%
“…At the highest GO content, aggregation of GO may begin to take place and this degrades the mechanical properties. The decrease of the mechanical properties above a certain GO content was observed in many studies 26,27) . In many studies 13,18,19,28,29) , the incorporation of GO or functionalized graphene results in the decreased EB.…”
Section: Resultsmentioning
confidence: 75%
“…. The spectrum of PCNTs shows the presence of two peaks at 3430 and 1600 cm −1 due to OH stretching vibration of the surface groups and conjugated CC bonds, respectively . The spectrum of SFCNTs exhibits peaks at 3415 cm −1 (OH stretching vibration), 2925 cm −1 (CH 2 stretching mode), 1675 cm −1 (CC stretching vibration), 1575 cm −1 (CH 2 bending mode), 1210 cm −1 (skeletal vibration involving the bridge SO stretch) and 1098 cm −1 (CC stretching) confirming presence of SDS in SFCNTs .…”
Section: Resultsmentioning
confidence: 86%